Ecological health - Gislason, Maya K. (Bingley, U.K. : Emerald, 2013)
Drawing on ecosystem thinking, complexity and postnormal science, Ecological Health offers a radical new way of thinking about the health issues of the 21st Century. This volume reflects on recent social scientific engagement with Ecosystem Health research and practice and sets out a vision for the future. While significant links between human health and the environment are increasingly evident, how to make sense of the interdependence of human health on natural systems is posing significant challenges. Ecological health is a new approach used by medics, public health practitioners, veterinarians, as well as social and natural scientists who study health at the nexus between human, animal and ecological systems. This volume is a reference tool offering a sociological analysis of the interrelationship between society, earth systems and health as conceptual frameworks. The authors provide methodological tools for conducting social science research that integrates social, natural and medical systems. It will appeal to a broad audience of researchers and practitioners who currently work in the arena of ecology and health and as well as those interested in expanding their research.
Introduction / Maya K. Gislason, Gillian A. Bendelow -- Expanding the social : moving towards the ecological in social studies of health / Maya K. Gislason -- Towards a critical approach to ecohealth research, theory and practice / Crescentia Dakubo -- Exploring aboriginal peoples connection to country to strengthen human-nature theoretical perspectives / Jonathan Yotti Kingsley, Mardie Townsend, Claire Henderson-Wilson -- Tibetan protest self-immolation in China : reflections on ecology, health and politics / Colin D. Butler -- Ecohealth through an ability studies and disability studies lens / Gregor Wolbring -- Structural vulnerability and narrative : sensitising concepts for understanding the health impacts of climate change / Rebecca Moran, Julie Hollenbeck, Cassandra Phoenix -- Health and environmental politics in the United States : a historical perspective / Jennifer Thomson -- Exploring the links between HIV/AIDS and forests in Malawi : morbidity, mortality, and changing dependence on forest resources / Joleen Timko -- Drops and hot stones : towards integrated urban planning in terms of water scarcity and health issues in Leh Town, Ladakh, India / Daphne Gondhalekar ... [et al.] -- The ecology of dying : commodity chains, governance, and the medicalization of end-of-life care / Christine Vatovec, Laura Senier, Michael Mayerfeld Bell -- Why is an integrated social-ecological systems (ISES) lens needed to explain causes and determinants of disease? A case study of Dengue in Dhaka, Bangladesh / Parnali Dhar Chowdhury, C. Emdad Haque -- Perpetuating a reductionist medical worldview : the absence of environmental medicine in the American ADHD clinical practice guidelines / Manuel Vallée -- A sustainable development agenda for the UK National Health Service (NHS) : an organizational learning model for defining and supporting goals / Claire Marsh -- Environmental health risk governance in practice : lessons learned from a Flemish case study approach / Kristien Stassen, Pieter Leroy -- Oceans and human health in the Caribbean region / Alana Malinde S.N. Lancaster, Lyndon F. Robertson.
Print version record
Keywords: Social Science -- General; Social Science -- Disease & Health Issues; Sociology; Medical sociology; Environmental health; Human ecology -- Health aspects; Human beings -- Effect of environment on